The Role of Digital Marketing and Infrastructure as Promotional Media in Increasing the Number of New Students at Karya Wijaya Kusuma Vocational School – Jakarta - Hugeng Song Arsanto; Irwan Tanamas; Auderey G.D. Hats; Marisi Pakpahan (International Journal Business, Management and Innovation Review, 2024)
This research aims to determine the role of digital marketing as a promotional media instrument that can influence the public's assessment and confidence in an educational institution. The application of digital marketing and infrastructure as promotional media allows schools to reach a wider audience and interact in a personal and interactive manner. This research uses a descriptive qualitative approach using a case study model. Data collection techniques are carried out through observation, interviews and documentation studies. The results of this research explain that the role of digital marketing and infrastructure as promotional media at the Karya Wijaya Kusuma Vocational School has been achieved well based on three main components, namely Digital Marketing Strategy, Investment in facilities, and periodic evaluation. The most important findings from this research are the form of promotional media and infrastructure campaigned by the Karya Wijaya Kusuma school, the role of digital marketing and infrastructure at the school, there is an increase in the number of new students. The synergy between digital marketing and improving infrastructure has proven effective in increasing the number of new registrants. Digital marketing creates initial awareness and interest, while good facilities and infrastructure provide additional confidence for prospective students and parents.